Comparison of microbiota structure in reproductive tract of Yanbian cattle and Yanhuang cattle - Teng, Yunkun; Feng, Shuai; Gu, Zhuoxuan; Hou, Chunqi; Xu, Haoran; Li, Zhiqiang; Zhao, Jing; Fang, Yi; Ma, Xin; Liu, Hongyu; Guo, Jing; Wang, Jun; et al. (Frontiers in Microbiology, 2024)
Microbiota in the reproductive tract of cattle play a vital role in maintaining normal reproduction. However, the information on microbiota in different parts of reproductive tracts with different genetic background is few. The aim of the present study was to describe and compare the microbiota in vagina, cervix and uterus of Yanbian cattle and Yanhuang cattle. The results showed that microbial diversity increases from the vagina to the uterus. The top three bacterial phyla in bovine reproductive tract were Proteobacteria, Firmicutes and Bacteroidetes, accounting for more than 85%. From the vagina to the uterus, the relative abundance of Proteobacteria gradually decreased, while that of Firmicutes gradually increased.Phylum-level Firmicutes and genus-level UCG_010 were significantly enriched in the uterus of Yanbian cattle and Yanhuang cattle. Comparing the same parts of the two breeds, it was found that there was no significant difference in alpha diversity, but significant differences in beta diversity. In addition, microbiota with significant differences in the relative abundance of the reproductive tract were found. These findings lay a foundation for a comprehensive understanding of the structure of the genital tract microbiota of cows and its regulatory mechanisms.